Frequency of Anemia and its Types in Type II Diabetes Mellitus Patients without Renal Insufficiency - Ifrah Sarosh, Romana Ghafoor, Abdul Haseeb, Jaweria Saeed, Faiza Shafqat, Zertaj Kashif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus is one of the most common diseases of twenty-first century. Anemia is 2 to 3 times more common in Diabetic Mellitus patients as compared to normal individuals. Aims and Objective: We aimed to determine the frequency of anemia and its types in patients with type II diabetes mellitus without renal insufficiency. Methodology: It was an observational study done at the Medicine department of Nishtar Medical University and Hospital Multan for six months from December 2021 to May 2022. We included 200 diabetic patients aged between 18 to 80 years. All the patients had normal renal function test with the duration of diabetes being more than one year. Men with HB level < 13.0g/dL and women with a HB level < 12.0g/dL were considered to have anemia. Data was collected through a structured proforma. SPSS version 20.0 was used for data analysis. Results: Out of 200 patients, there were 118 (59%) females and 82 (41%) males. The mean age of patients was 49.64±13 yrs (25-79 yrs.), the mean duration of diabetes was 5.98±4.65 (1-25 years), mean hemoglobin level was 11.97±2.3 mg/dl (7-16mg/dl) and mean MCV was 86.7±9.5 (64-110). Seventy-eight (39%) had anemia, and the remaining 122 (61%) patients were non-anemic. Out of 78 anemic patients, 33 (42.3%) had microcytic anemia, 33 (42.3%) had normocytic anemia and 13 (16.6%) had macrocytic anemia. 108 (54%) had controlled diabetes mellitus and 92 (46%) had uncontrolled diabetes mellitus. There were 52 (66.7%) anemic patients with uncontrolled diabetes and 26 (33.3%) with controlled diabetes (P-value= 0.000). Conclusion: We concluded that diabetics patients without renal insufficiency have a significant risk of anemia. Our findings also revealed that in diabetic patients without renal insufficiency, poor glycemic management, longer disease duration, and old age significantly increase the risk of anemia.